Fabrication and strength analysis of humanoid focusing mechanism - Tsai, Yao-Chuan (2013)
The human eye was constructed from the soft lens and the ciliary muscle. The ciliary muscle induces force on the lens through an array of fibrillar structure that surrounds the lens. In this paper, the humanoid focusing mechanism which consists of parylene nanofibers and soft polymer lens was presented and demonstrated. The soft polymer lens was constructed of a PDMS envelope and a silicone core. The parylene nanofrillar film was fabricated by anodic aluminum oxide (AAO) template and used to adhere to the lens and to transfer the accommodation force. For verifying the function of the fibrillar structure around the lens, an experiment stage was set up to test the normal and shear strength and to compare two bonding conditions: fibrillar bonding and plate bonding. Besides, the relation between the focal length and applied force was estimated by the lens contour measurement and the laser light focusing measurement.